Grounds for Cooperation in the Radicalisation Governance Milieu?: a Qualitative Exploration of Stakeholder Issue Frames of Online Radicalisation - Oorschot, Irene van (Perspectives on terrorism, 2024)
In the study of online radicalisation, little attention has been paid to the way local stakeholders within the broader online radicalisation milieu define, frame, and problematise online radicalisation. As these conceptions and problematisations are crucial to the possibility of cooperation and coordination between them, this lacuna represents a curious oversight. Drawing on a cross-national and highly diverse sample of stakeholders, including law enforcement actors, religious and community leaders, policy-makers and activists, and scientific experts, we inductively identify four largely shared ‘issue frames’. We conceptualise issue frames as ways of organising knowledge and meaning, and as crucial to the way problems - in this case online radicalisation - come to be defined, constructed, and contested by various social actors. Uncovering four shared issue frames, we show how stakeholders commonly 1) highlight the tension between individual and social understanding of radicalisation; 2) reflect on the national embeddedness of radicalisation discourse; 3) comment on the complex politics of online radicalisation monitoring; and 4) warn against the mysteries inherent in algorithmic surveillance and control. Demonstrating that these specific issue frames are largely shared between a highly diverse group of stakeholders, we emphasise the need for cooperation and coordination between these actor groups.